Pengaruh Pemberian Pakan dari Limbah Penetasan Telur Ayam terhadap Media Pemeliharaan Lobster Pasir (Panulirus Homarus) - Amanda, Dwika Melani; Azhar, Fariq; Scabra, Andre Rachmat; Syukur, Abdul; Amin, Muhammad; Faturrahman, Faturrahman (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
Chicken egg hatching waste flour can be an alternative to replace expensive spiny lobster feed because apart from being waste it is also cheap and easy to obtain. The purpose of this research is to determine the effect of feeding chicken egg hatching waste on the water quality of spiny lobster (Panulirus homarus). This research used an experimental method with a Completely Randomized Design (CRD) consisting of 4 treatments with 3 replication. The results of the study showed that the composition of chicken egg waste can influence temperature, DO, pH, salinity, nitrate, nitrite, ammonia, absolute weight growth, absolute length growth, Specific Growth Rate, Feed Conversion Ratio and Survival Rate of spiny lobste.